Comparative Effectiveness of Mouthwash Containing Chlorhexidine 0.12% and Cetylpyridinium Chloride 0.1% with Chlorhexidine 0.2% against Porphyromonas gingivalis - Karissa Adiela Sutanto; Vinna Kurniawati Sugiaman; Henry Yonatan Mandalas (Denta Journal Kedokteran Gigi, 2025)
Background: Periodontitis is an inflammatory disease that affects the supporting tissue of teeth and causes damage to the periodontal ligament and alveolar bone, generally caused by microorganisms. Chronic periodontitis is often caused by gram-negative anaerobic bacteria, especially Porphyromonas gingivalis. Mouthwash active ingredients that frequently used such as chlorhexidine (CHX) or cetylpyridinium chloride (CPC) have an antibacterial effect and prevent plaque formation. Objective: This research aims to compare the effectiveness of mouthwash containing CHX 0.12% and CPC 0.1% with CPC 0.2% on the bacterium Porphyromonas gingivalis ATCC 33277. Materials and Methods: This research is an experimental laboratory by giving treatment to Porphyromonas gingivalis with mouthwash CHX 0.12% and CPC 0.1%, CHX 0.2%, and distilled water as the negative control, then calculating the inhibition zone for each treatment and continued with One-Way ANOVA test. Results: The result showed the largest average of the inhibitory zone diameter was on CHX 0.2% which was 12,7 mm. Meanwhile, mouthwash containing CHX 0.12% and CPC 0.1% showed an average diameter of inhibitory zone resulted in 10,97 mm. Conclusion: In conclusion, CHX 0.2% has greater ability of inhibitory than mouthwash containing CHX 0.12% and CPC 0.1% against the growth of Porphyromonas gingivalis.